Medicinal and immunological aspects of bacteriophage therapy to combat antibiotic resistance - Isra Noor; Muhammad Hassan Nasir; Aneeq Ur Rehman; Noof Javed; Warda Waheed; Areeba Waheed; Ishmal Jamil; Wajeeha Shafiq; Muhammad Haseeb; Divya Dhawal Bhandari; Hitesh Chopra; Ahmad Syibli Othman (Open Exploration Publishing Inc., 2024)
Bacteriophages are viruses that infect bacterial cells and use their machinery to reproduce. This unique characteristic holds immense promise for combating antibiotic-resistant bacterial infections, a growing global threat. There are two types: one of them is named temperate phages, which inject their genomic material into bacteria and integrate into the host's genome, while the second one is entitled as lytic phages that subdue the entire metabolism of the bacterium for the synthesis of its genome and proteins, including lytic proteins involved in breaking bacterial cell membrane and release of novel phages. In addition, phage therapy can be expressed through anti-biofilm activity and by triggering innate and adaptive immune cells responses. Moreover, no adverse effects of phage therapy have been reported. However, phage therapy is still grim for many and could influence some interpretations related to immune response, bacteriophage selections, and phage resistance in the future.